Development of Mangosteen Peel Flour as a Functional Food Ingredient to Support Entrepreneurial Independence in Village - Cahyani, Yasmin Athiyyah; Mulyati, Ade Heri (Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Pakuan, 2025)
Sipak Village in Jasinga, Bogor Regency, has great potential for mangosteen production, yet it remains limited to fresh fruit sales, leading to increased peel waste. Through the PPK Ormawa program, students introduced the innovation of processing mangosteen peel into functional flour via blanching, drying, and grinding to retain bioactive compounds like xanthones and flavonoids. The program involved surveys, training, production, business mentoring, and marketing strategies. Final products included syrup, tea, and cookies under the brand Queens Flour. This initiative improved community skills, fostered local entrepreneurship, and reduced organic waste in a sustainable manner.